2014
DOI: 10.1177/0269216314522317
|View full text |Cite
|
Sign up to set email alerts
|

What justifies a hospital admission at the end of life? A focus group study on perspectives of family physicians and nurses

Abstract: A number of situations have been identified in which nurses and family physicians consider a hospital admission to be justified. Adequate advance care planning and improved psychosocial support to both family and professional caregivers could reduce the number of hospital deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 38 publications
(42 reference statements)
0
67
0
Order By: Relevance
“…For the other countries, one possible explanation might be that older people with dementia who are more highly educated, or married, as well as those aged 65 to 79 and men in general, are more likely to reside at home, but are unable to remain there until the very end of life, resulting in an end-of-life hospital admission and hospital death. 9,36,38 One Dutch study found that for older people, 2 main scenarios were likely: residing in a nursing home, lowering the chances of hospital death, or staying at home as long as possible, with a higher likelihood of hospital death. 39 Consequently, it could be suggested that among older people with dementia, those who are most likely to reside at home, in particular, should be supported by specialist palliative care services to reduce the number of hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the other countries, one possible explanation might be that older people with dementia who are more highly educated, or married, as well as those aged 65 to 79 and men in general, are more likely to reside at home, but are unable to remain there until the very end of life, resulting in an end-of-life hospital admission and hospital death. 9,36,38 One Dutch study found that for older people, 2 main scenarios were likely: residing in a nursing home, lowering the chances of hospital death, or staying at home as long as possible, with a higher likelihood of hospital death. 39 Consequently, it could be suggested that among older people with dementia, those who are most likely to reside at home, in particular, should be supported by specialist palliative care services to reduce the number of hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although hospitalization might be considered justified in some circumstances, 9 it also has been suggested that the acute hospital setting is not an adequate place for end-of-life care and death for chronic terminally ill patients and this might be particularly so for patients with advanced dementia. 11e13 In this setting, they may be more likely to experience delirium, 14 falls, or other adverse events, 6,14e16 and often experience burdensome interventions or procedures that might be of little benefit, such as tube feeding.…”
mentioning
confidence: 99%
“…It is evident that preference for home as a place of death decreases as people get older and as the prospect becomes a more pressing reality. 51,59,[66][67][68][69] Evidence from qualitative studies suggests that terminally ill patients may often feel uncertain about their preferences, which are likely to change throughout the course of illness. Such preferences are often not formulated clearly, especially in the face of uncertainty about what will happen throughout the experience of dying.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…Evidence accumulates about the complex situational factors underlying decisions and the varied preferences which may subsequently be expressed. 22,59,66,69,142,180 The focus on place has deflected attention from how death is experienced in different settings. 69,72,73,77,179 Patients tend to adopt a pragmatic stance to place of death.…”
Section: 132139mentioning
confidence: 99%
“…Other treatments are offered on site, as they are in other comparable contexts where hospital admissions are also infrequent. 38 The HC services considered in this study were not equipped to deliver specialized or intensive treatments. 27 In an older US study, HC patients were less often admitted to the hospital and less often exposed to feeding tubes and IV medications, 39 but those patients were in better health (more independent and with a better cognitive performance score) compared with the patients in our study.…”
Section: Typology Of Critical Decisionsmentioning
confidence: 99%